Measuring Service Quality in Distribution Logistics Using SERVQUAL and AHP: A Case Study in a Pharmaceutical Wholesaler in Turkey - Karpuzcu, Harika (2006)
Service quality has gained quite a lot attention in the last two decades from both academics and private sector, due to its significant influence on consumer perceptions of performance. Various tools have been developed to measure service quality accurately, yet there seems not to be a single universally agreed method that serves properly to the purpose. This study attempted to adapt SERVQUAL and AHP techniques for developing two instruments for service quality measurement in a physical distribution service setting. The tools are exercised by a sample of customers of the focus company and several results are obtained. Service quality attributes important for the business context are identified through detailed analysis of relevant literature and gathered into the service quality measurement tools. Sample responses are compared on various bases; responses to PWSQ (the SERVQUAL variation model) and AHP questionnaires are found to be quite different. Gap scores obtained from PWSQ instrument suggested that most of the customers were dissatisfied with the service quality, whereas only a small number of respondents seemed to be dissatisfied with the service quality as a result of AHP model analysis. The significant differences between the results of the two methods suggested that the approaches differed in terms of their capabilities in reflecting customer opinions accurately and depending on the various comparisons made, the AHP variation model is claimed to be a more proper tool in measuring service quality.